Coronary artery fistula: key clinical and therapeutic management aspects. A comprehensive literature review - Turek, Łukasz; Domagała, Szymon; Sadowski, Marcin; Janion, Marianna (Medical Studies/Studia Medyczne, 2023)
Coronary artery fistula (CAF) is a rare structural anomaly characterized by an abnormal connection between a coronary artery and a vessel or cardiac chamber. The natural history of CAF is highly variable, and it may cause significant cardiac morbidity; however, it has yet to be fully elucidated. Although uncommon, CAF is an important consideration in the differential diagnosis of common pulmonary and cardiac issues, such as dyspnoea or chest pain. While small fistulae are often asymptomatic and require no treatment, symptoms and complications, such as myocardial infarction, heart failure, or arrhythmias, especially in cases of significant fistula size, may necessitate percutaneous or surgical closure. The management of each fistula is tailored to its specific characteristics. Notably, most studies on CAF are case reports with small patient cohorts, and several aspects of CAF management still lack clear guidelines.